Extension of time claim assessment in Malaysian construction industry: views from professionals / Norazian Mohamad Yusuwan and Hamimah Adnan. - Mohamad Yusuwan, Norazian; Adnan, Hamimah (Universiti Teknologi MARA Cawangan Selangor, 2018)
This paper aims to investigate the current practice of extension of time claim assessment by contract administrators and identify difficulties faced by them during the assessment process. Findings from the questionnaire survey revealed that poor factual evidence and flaws in claim presentation are the principal factors leading to delays in the assessment process. The findings imply that efficient contract administration and well-organised record keeping will lead not only to successful project management but also will increase the chances of a successful contractual claim. These findings are expected to offer a significant contribution to industry players, researchers and also academics, thus helping to identify areas for further improvement.